A qualitative study on the experience of empowerment from the perspectives of breast cancer survivors - Zebing Luo; Chujun Chen; Wanzhu Xu; Peiru Wang; Yiru Wang (Wiley, 2021)
Abstract Aim To describe the experience of empowerment for breast cancer survivors in order to increase quality of life after treatment. Design We adopted a qualitative design in this study. Methods A qualitative descriptive approach guided by interpretive description methodology as the theoretical framework was used in this study. Semi‐structured group and individual interviews were conducted with eleven female Chinese breast cancer survivors (mean age 54.18 years, 100% female). Results Many survivors reported that they continued to experience disease‐related discomfort from the physiological aspect, but they use multiple ways to improve quality of life. Breast cancer survivors experienced empowerment after treatment. Empowerment mainly required three components: a belief in good health, capability of self‐management and acquisition of a good social support system.